Primary Biliary Cirrhosis and Type II Autoimmune Polyglandular Syndrome - Mark Ram Borgaonkar; David Geoffrey Morgan (Canadian Journal of Gastroenterology)
A 45-year-old female was diagnosed with Hashimoto’s thyroiditis in 1976 and Addison’s disease in 1979. At that time, her antimitochondrial antibody (AMA) level was elevated at 1:32. She subsequently developed premature ovarian failure and type I diabetes mellitus. In 1996, she became jaundiced with a cholestatic enzyme pattern. AMA was positive at a titre of 1:256. A liver biopsy confirmed the diagnosis of primary biliary cirrhosis (PBC). She underwent a liver transplantation in January 1998. This is the first report of PBC in association with type II autoimmune polyglandular syndrome. The association of PBC with other organ-specific autoimmune diseases supports an immune-mediated pathogenesis and may have implications in further studies of PBC.